1986
DOI: 10.1103/physrevc.34.2358
|View full text |Cite
|
Sign up to set email alerts
|

Angular momenta of intermediate width structures inC12+O

Abstract: Intermediate width resonance-like structures in the ' C+'~0 system have been studied via inelastic scattering to the 'so(02+) state. The dominant partial waves contributing to several structures have been determined by analysis of excitation functions at zeros of Legendre polynomials.The results disagree vrith spins extracted from angular correlation measurements in non-spin-zero channels.Measurement of the spins of proposed intermediate width structure resonances in elastic and inelastic-scattering channels h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…= 40 • , however, the angular distributions were closely in phase with a Legendre polynomial of order 14. Furthermore, an analysis of the angular distributions of the type suggested by Balamuth et al [24] and Chapuran et al [25] at angles corresponding to zeroes of Legendre polynomials for these backward angles suggested that the backward-angle data were more consistent with l = 14 than with any other partial wave. Clearly, the results for the current resonance in the mismatched 0 + 2 + 2 + 1 channel are different from those of the more well-matched 0 + 1 + 2 + 1 , 2 + 1 + 2 + 1 , and 3 − 1 + 0 + 1 excitations.…”
mentioning
confidence: 92%
“…= 40 • , however, the angular distributions were closely in phase with a Legendre polynomial of order 14. Furthermore, an analysis of the angular distributions of the type suggested by Balamuth et al [24] and Chapuran et al [25] at angles corresponding to zeroes of Legendre polynomials for these backward angles suggested that the backward-angle data were more consistent with l = 14 than with any other partial wave. Clearly, the results for the current resonance in the mismatched 0 + 2 + 2 + 1 channel are different from those of the more well-matched 0 + 1 + 2 + 1 , 2 + 1 + 2 + 1 , and 3 − 1 + 0 + 1 excitations.…”
mentioning
confidence: 92%